Emerging Technologies and Implications for Financial Cybersecurity - Smith, Sean Stein (International Journal of Economics and Financial Issues, 2019)
Emerging technology tools, such as blockchain, cryptoassets, robotic process automation, and artificial intelligence continue to change and influence the economic landscape at both a macro level and in different professional sectors. Pointedly, cybersecurity – far from being reduced in importance or relegated to secondary importance – continues to factor as a core consideration for management professionals. Accounting and financial services practitioners at large have long played a role in advising clients on technology matters as well as integrating technology into internal processes. As technology integration continues to accelerate, and fundamentally change how business processes function, practitioners must be able to assess and explain the implications of these tools on both internal and external processes. Written with both a practitioner and academic audience in mind, this research also leaves the door open for future research, analysis, and discussion. Keywords: Blockchain, cryptoassets, robotic process automation, artificial intelligence, cybersecurity JEL Classifications: G, M DOI: https://doi.org/10.32479/ijefi.8844